Encouraging Responsible Tourists: Strategies for Sustainable Tourism - Apay Safari; Adrian Agoes (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community service activity aims to socialize the concept of responsible tourism to Generation Z travelers in support of sustainable tourism. The method employed involves inviting 20 Vocational School of Tourism students to participate in a city tour using Bandros HPI in Bandung and delivering the concept interactively and enjoyably. Understanding that acting as responsible tourists is the most practical and easily understood approach for Generation Z, serving as the operationalization of sustainable tourism concept, the results of this activity indicate an increased awareness among the Vocational School of Tourism students regarding the importance of behaving as responsible tourists. Therefore, it can be concluded that socialization activities like this should be conducted more widely among Generation Z to enhance awareness of responsible tourism as the embodiment of sustainable tourism